Application of cellulose acetate for controlled release of thymol. (20th August 2016) - Milovanovic, Stoja; Markovic, Darka; Aksentijevic, Ksenija; Stojanovic, Dusica B.; Ivanovic, Jasna; Zizovic, Irena
Highlights: Cellulose acetate is a promising carrier for controlled release of thymol. Thymol release, depending on its content and release medium, is up to three days. Changes in the CA morphology are by the influence of thymol content. Thymol impregnated CA shows antibacterial activity, among others against MRSA. Abstract: Cellulose acetate (CA) was investigated as a carrier towards development of material with controlled release of thymol as a natural substance with strong antibacterial properties using high pressure techniques. Effect of thymol content on CA was confirmed by SEM, FTIR and DSC methods. Kinetic of thymol release from CA was tested using simulated gastric and intestinal fluids (hydrochloric acid and phosphate buffer saline). Results were correlated with Korsmeyer-Peppas and Weibull model. Depending on the thymol content and chemical nature of the release medium, the time of thymol release varied from one to three days indicating CA as a promising carrier of thymol with potential uses from medicine to agriculture. The impregnated CA showed antibacterial activity against 23 tested bacterial strains including methicillin-resistant Staphylococcus aureus (MRSA) which is particularly important bearing in mind that this strain causes fatal infections in humans and animals.